Non-prototypicality by (discontinuous) reduplication: The N-non-N construction in Italian - Francesca Masini; Jacopo Di Donato (Zeitschrift für Wortbildung)
This paper contributes to the research on the morphological expression of approximation by analysing the discontinuous reduplication pattern N-non-N in Italian, giving rise to complex nominals (e.g. sapone non sapone lit. soap neg soap ‘non-soap/soap-free cleanser’). The analysis is based on a dataset of 4609 tokens and 692 types extracted from corpora and annotated for orthographical, phonological and categorical parameters. Given its unpredictable formal and semantic properties, N-non-N is analysed as a semi-schematic and productive construction, which is hypothesized to have emerged microdiachronically from the entrenchment and reanalysis of the expression tessuto non tessuto ‘nonwoven fabric’. We claim that the N-non-N construction bears a general function of ‘non-prototypicality’ and produces expressions with complex and specific meanings that are generated in context, by deviating from the ‘prototypical’ N concept in various ways. Despite its productivity, very few N-non-N expressions are conventionalised, making this device similar to other approximative strategies and to evaluative morphology in general.